RESPONS VIABILITAS DAN PERTUMBUHAN VEGETATIF TIGA VARIETAS TANAMAN BAWANG MERAH (Allium ascalonicum L.) ASAL BIJI TRUE SHALLOT SEED (TSS) PADA PERLAKUAN KOMBINASI MEDIA TANAM - Kartina kartina; Imas Rohmawati; Rian Septia Nugraha (Jurnal Agroekoteknologi, 2021)
The research was aimed to know the response of viability and vegetative growth of three shallots varieties (Allium ascalonicum L.) from seeds TSS (True Shallot Seed) on combination treatment of plant media. This research was conducted at the Screen House of Center for Protection of Food Crops, horticulture and plantations Serang Province of Banten from September until November 2020. The research used a Randomized Completely Design consisted of two factors. The first factor was the varieties, consisted of three levels were varieties Bima Brebes, Lokananta and Sanren. The second factor was the combination of plant media, consisted of three levels were (soil + compost cow manure), (soil + husk charcoal) and (soil + compost cow manure + husk charcoal). The result showed that varieties Lokananta affected the parameters day of germination (4.56 day), maximum growth potential (87.33%), power germination (87.78%), growth rate (5.78%/day) and percentage normal sprouts (80.89%), height of plant at 14, 21, 28, 35 and 42 DAP (Day After Planting) and number of leaves at 14, 21, 28, 35 and 42 DAP. Combination of plant media soil + husk charcoal gave the best effect on the parameters day of germination (4.67 day), maximum growth potential (88.00%), power germination (88.44%), growth rate (5.76%/day) and percentage normal sprouts (80.67%), height of plant at 14, 21, 28, 35 and 42 DAP and number of leaves at 14, 21, 28, 35 and 42 DAP. There was no interaction between varieties and combination of plant media except for the day of germination parameter.